Mediation of the Association Between Physical Exercise and Depressive/Anxiety Symptoms by Pain and Sleep Problems Among Older Adults - Namkee G. Choi PhD; Bryan Y. Choi MD, MPH; C. Nathan Marti PhD (Gerontology and Geriatric Medicine, 2024)
In this study, based on the 2022 National Health and Aging Trend Study ( N  = 5,593, age 65+), we examined direct associations between moderate and vigorous physical exercise (PE) and depressive/anxiety symptoms as well as bothersome pain and sleep problems. We then examined if the association between PE and depressive/anxiety symptoms would be partially mediated by the effects of PE on bothersome pain and sleep problems. Results from a path model showed that controlling for sociodemographic and health statuses, PE was negatively associated with depressive/anxiety symptoms and bothersome pain, but it was not significantly associated with sleep problems. The mediation analysis showed that 10% of the total effects of PE on depressive/anxiety symptoms was indirect effects of PE on bothersome pain. This study is important as it examined the associations among PE, pain, sleep, and depression/anxiety in community-dwelling older adults in their natural environments. Healthcare and social service providers for older adults need to emphasize the importance and benefits of PE for older adults’ physical and mental health. Easy access to venues for PE is also important.